SMOKING AS A RISK FACTOR FOR CARDIOVASCULAR AND CEREBROVASCULAR DISEASES: PREVALENCE, IMPACT ON PROGNOSIS, POSSIBLE SMOKING CESSATION STRATEGIES AND THEIR EFFECTIVENESS. Part 2. Advantages of quitting smoking. Strategies to quit smoking - O. D. Ostroumova; I. I. Kopchjonov; T. F. Guseva (Рациональная фармакотерапия в кардиологии, 2018)
The immediate and remote benefits of smoking cessation are considered. Within one year after quitting smoking the ischemic heart disease (IHD) risk will be 2 folds lower than the risk in smoking patient. Within 15 years the IHD risk declines to non-smoking population level. After 5-15 years after quitting smoking the risk of stroke also declines to non-smoker risk. Smoking cessation prior to cardio surgical intervention leads to reduction of complications incidence by 41%. Smoking cessation significantly reduces the risk of developing stable and unstable angina, acute myocardial infarction, cardiovascular death, transient ischemic attack, ischemic stroke, subarachnoid hemorrhage, intracerebral hemorrhage, peripheral arterial diseases, abdominal aortic aneurysm at any age, in both sexes in comparison to patients who continue to smoke. Smoking cessation is the most cost-effective strategy of cardiovascular disease prevention. Today, the most effective smoking cessation strategy is the identification of smokers and continuous advice on smoking cessation, and offer of the appropriate medication, primarily varenicline. The article contains data from a number of studies showing that varenicline is an effective and safe drug for tobacco dependence treatment, in particular, in patients with acute and chronic cardiovascular disease.